A Delicate Surgical Resection to Treat a Proximal Pulmonary Adenoid Cystic Carcinoma. (3rd July 2021) - Belloumi, N.; Baili, H.; Abdennadher, M.; Habbouria, C.; Bachouch, I.; Bouassida, I.; Zairi, S.; Chermiti Ben Abdallah, F.; Fenniche, S.; Zribi, H.; Marghli, A.
Abstract : Pulmonary adenoid cystic carcinoma (PACC) is an exceedingly rare tumor of low-grade malignancy. Diagnosis is often late, so the tumoral process may be huge at presentation. Surgical resection could be challenging, and the recurrence rate would be greater. We report, hereby, a case of proximal PACC with involvement of the carina in a young male adult, without respiratory distress. Surgical resection was performed through a left pneumonectomy followed by a complex trachea-bronchoplastic procedure. During the operative time, the assisted ventilatory mode was carefully chosen. No adjuvant treatment was needed. Our patient is still under clinicoradiological surveillance and remains disease-free.